PROTECTION OF CHILDREN IN THE GENEVA CONVENTIONS: YEMENI ARMED CONFLICT CASE STUDY (2015-2019) - Zulkarnain, Zulkarnain; Putri, Tiara Ambarsari (Journal of Social Political Sciences, 2020)
Children are our future and therefore must be protected, but children in Yemen are still faced with murder, maiming and many gross human rights violations during the long civil war. They are the group most affected by the conflict more than any other group of society. Destroying their home means they have to live in constant danger; the death of their parents left them orphaned; bombing schools and assaulting teachers will affect their future; and the physical and mental violence caused by war leaves eternal scars in their hearts. This study aims to determine how the UN Security Council responds to child violations that occur in the Yemeni armed conflict. This research is a descriptive qualitative research with the concept of conflict resolution and child protection in the Geneva Conventions as an analytical framework. The results of this study indicate that warring parties in Yemen have failed to protect Yemeni children, while the UN Security Council's efforts to hold them to account and improve child protection are still inadequate.